Loyalitas Pengguna Aplikasi MyTelkomsel: Determinasi Kepuasan dan Kepercayaan Berbasis Customer Lifetime Value (CLV) - Rendi Eka Herlinton; Rohimat Nurhasan; Fikri Fahru Roji (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to examine the influence of satisfaction and trust on Customer Lifetime Value (CLV) among users of the MyTelkomsel application. The research is motivated by the low level of user loyalty, despite the company’s efforts to introduce various digital features designed to enhance customer engagement. In the face of increasingly competitive digital service markets, understanding the key drivers of loyalty is essential. Employing a quantitative approach with an explanatory design, the study involved 100 purposively selected active users of the application. Data were collected through an online questionnaire using a four-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both satisfaction and trust have a significant positive effect on CLV, highlighting the importance of delivering a pleasant user experience and maintaining trust in the application's reliability to foster long-term loyalty. This research contributes to the theoretical framework of value-based loyalty and offers practical implications for telecommunications companies in developing adaptive relational marketing strategies in the digital era.